Looking inside the black box—semantic investigations on a frequently used expression beyond AI - Attar, Patrizia; Buresch, Franziska; Köhler, Anna; Hanauska, Monika (Frontiers in Communication, 2025)
Talking about Artificial Intelligence (AI) as a black box is a current phenomenon in scientific communication as well as in journalistic reporting on this topic. Yet, for several years we can observe an increasing use of the expression black box in further contexts like economics or politics not related to AI. This leads to the question of which aspects of meaning are associated with the expression and how the respective context of use might influence the constitution of the specific semantic features. Furthermore, it raises the question, which evaluative features accompany the expression as this might have an impact on the perception of the entity referred to as a black box. In our paper, we investigate these questions based on 288 contemporary articles from German speaking journalistic publications. Our method combines a qualitative content analysis with approaches from semantic theory of use and discourse semantics. The results indicate that the expression black box has developed a wide range of supplementary semantic features as lack of knowledge, uncertainty or (lack of) traceability through the use in varied contexts such as economics, politics or biochemical processes. This shapes the conceptualization of the term black box in contemporary language use, which also affects the conceptualization of AI in return whenever it is referred to as a black box.